Using emulated clinical trials to investigate the risk of being diagnosed with psychiatric ill health following the cancer diagnosis of a sibling. - Sara Kjellsson; Kristiina Rajaleid; Bitte Modin (PLoS ONE, 2024)
Background The sibling bond is often the longest relationship in an individual's life, spanning both good and bad times. Focusing on the latter, we investigated whether a cancer diagnosis in one adult sibling is predictive of psychiatric illness in the other, and if any such effect differs according the 'sociodemographic closeness' between the siblings in terms of sex, age, education, marital status and residence. Methods We used hospital records to identify psychiatric diagnoses (2005-2019) in a Swedish total-population cohort born in 1953, and cancer diagnoses (2005-2017) in their full siblings. By means of emulated clinical trials, the cohort member's risk of a diagnosis within two years following a first exposure (or non-exposure) to a sibling's cancer was analyzed through Cox regression. Results Exposed cohort members had a higher risk of psychiatric diagnosis than unexposed (HR = 1.15; CI: 1.08-1.23), with men displaying a higher risk (1.19; CI: 1.09-1.31) than women (HR = 1.11; CI: 1.01-1.22). Sub-analyses of the exposed group showed that women with a cancer-stricken sister had a higher risk of adverse psychiatric outcomes (HR = 1.31; CI: 1.07-1.61) than women with a cancer-stricken brother. Furthermore, unmarried cohort members ran a higher risk, both when the cancer-stricken sibling was married (HR = 2.03; CI: 1.67-2.46) and unmarried (HR = 2.61; CI: 2.16-3.15), than in cases where both siblings were married. No corresponding difference were detected for 'closeness' in age, education and residence. Conclusions In line with theories of linked lives, our findings suggest that negative events in one sibling's life tend to 'spill over' on the other sibling's wellbeing, at least during the 15-year-long period leading up to retirement age.